2018
DOI: 10.14740/gr944w
|View full text |Cite
|
Sign up to set email alerts
|

Internists’ Perceptions of Proton Pump Inhibitor Adverse Effects and Impact on Prescribing Practices: Results of a Nationwide Survey

Abstract: BackgroundObservational studies have linked proton pump inhibitors (PPIs) with serious adverse effects. The study aimed to evaluate internists’ perceptions of PPI harms and effects on prescribing.MethodsThis was an online survey of a representative sample of the American College of Physicians in 2013. We queried familiarity with and concern about PPI adverse effects (1 - 7 Likert-type scales, anchored by “not at all” and “extremely”). We also asked how frequently (often, sometimes, rarely, or never) participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It is apparent from our survey that many patients are obtaining their information from non‐physician sources, a finding not captured in the internet survey. The same authors surveyed primary care physicians and reported similar findings to the primary care MDs in our study, however, did not report information on GI MDs perceptions . Our sample of physicians consisted of academic physicians, whose views and knowledge may differ from attending physicians who are not in academic practice, offering opinions from an additional physician population.…”
Section: Discussionmentioning
confidence: 73%
“…It is apparent from our survey that many patients are obtaining their information from non‐physician sources, a finding not captured in the internet survey. The same authors surveyed primary care physicians and reported similar findings to the primary care MDs in our study, however, did not report information on GI MDs perceptions . Our sample of physicians consisted of academic physicians, whose views and knowledge may differ from attending physicians who are not in academic practice, offering opinions from an additional physician population.…”
Section: Discussionmentioning
confidence: 73%
“…Physician concern about adverse effects of PPI therapy have been suggested, with 52% of internal medicine physicians self-reporting they sometimes or often changed a patient’s prescription from PPI therapy to H2 antagonists. 22 A prior study suggested H2 antagonists were prescribed more frequently than PPIs in patients with uninvestigated dyspepsia (88.1% versus 47.4%, respectively). 13 However, the current study’s findings were consistent with guideline recommendations, and this increased usage of PPIs over H2 antagonists for acid suppression therapy may indicate guideline adherence in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey of internist members of the American College of Physicians, 98% reported having some concern about the adverse effects of PPIs, with 63% altering the dose, 52% switching to H2 blockers, and 44% discontinuing the PPI. 21 Moreover, patients are becoming more knowledgeable about their health care and may also have concerns about PPI treatment. 22 An association between PPI use and an increased risk for CAP was observed in our cohort with laryngeal/voice disorders.…”
Section: Discussionmentioning
confidence: 99%